Size‐Based Effects of Anthropogenic Pressures and Elephant Activity on Tropical Forest Carbon Stocks - Ankita Gupta; Camille DeSisto; Donald Midoko Iponga; Alfred Ngomanda; Vincent Maicher; Halina Malinowski; John R. Poulsen (Global Ecology and Biogeography, 2026)
Aim To evaluate how elephant activity and anthropogenic disturbances (logging, secondary forest conversion, and proximity to villages) influence aboveground carbon (AGC) stocks in tropical forests and how their effects vary across tree size classes. Location Gabon. Time Period 2013–2023. Major Taxa Studied Gymnosperms and angiosperms. Methods Using 260 one‐hectare forest plots across Gabon, we employed Bayesian modelling to quantify the effects of elephant activity and disturbances on AGC through changes in stand structure—that is, basal area (), tree height (), and wood density ()—across three tree diameter () classes: small (10 cm ≤ 30 cm), medium (30 cm 70 cm) and large ( 70 cm). Environmental covariates (temperature, precipitation, and soil characteristics) were also incorporated in our models to account for broader climatic influences and to isolate disturbance effects. Results Anthropogenic disturbances, particularly secondary forest conversion and proximity to villages, were strongly associated with reductions in AGC, driven by declines in , , and . By contrast, elephant activity increased in small and medium trees, suggesting long‐term contributions to forest compositional shifts and carbon storage potential. Size‐based analysis revealed divergent disturbance impacts across tree size classes that were not evident in whole‐plot summaries. Main Conclusions Elephant activity and anthropogenic disturbances influence AGC through distinct, size‐based pathways. While human activities reduce carbon stocks by altering forest structure, forest elephants enhance traits associated with carbon‐dense composition. Conservation strategies that integrate faunal interactions with forest management are essential to maintaining tropical carbon stocks under ongoing environmental change.

Anthropogenic and environmental factors are associated with frugivore interaction diversity - Camille M.M. DeSisto; Jennifer Kampe; Alfred Ngomanda; Donald Midoko Iponga; Ankita Gupta; Charles L. Nunn; John R. Poulsen (Biological Conservation, 2026)

The biogeography of Gabonese savannas: Evidence from termite community richness and composition - Fidèle Evouna Ondo; Kathryn J. Jeffery; Robin Whytock; Katharine A. Abernethy; Pierre Couteron; Paul Eggleton; Claire Griffin; Nicolas J. Ostle; Aurelie‐Flore Koumba Pambo; Alfred Ngomanda; Josué Edzang Ndong; Catherine L. Parr (Journal of Biogeography, 2023)
Aim The mosaic of savannas that persists in the forest‐dominant Congo Basin is thought to be palaeoclimatic relics, but past biogeographical processes that have formed and maintained these systems are poorly understood. Here, we explored the post‐Pleistocene biogeography of Gabon's savannas using termites as biological indicators to understand historical and mechanistic factors influencing present‐day termite communities in the country's extant savannas. Location Gabon, Central Africa. Taxon Blattodea: Termitoidae. Methods Using standardised transect methods, we sampled termite communities in four disjunct modern savanna areas of Gabon: the centre (Lopé), the southeast (Batéké) and the south (Mayombe North and South). Termites at Lopé were collected in three habitats (annually burned savannas, savannas with a depressed fire regime and forest). We used DNA barcoding of the COII region to identify termite species and compared abundance, species richness and community composition across areas and habitats. Results Community composition differed greatly between Lopé and both Batéké and Mayombe savannas with Lopé being exceptionally depauperate and lacking characteristic savanna species. Within Lopé, termite abundance and diversity was highest in forests and lowest in annually burned savannas, with a gradual change in species composition across the forest–savanna gradient associated with fire history. Main Conclusions The absence of savanna typical species in Lopé savannas challenges current assumptions that these savannas were linked to the south/southeastern savannas during the Pleistocene and suggests a different evolutionary history. Lopé savannas may instead have opened as an isolated grassland and never have been contiguous with neighbouring savannas, or were isolated soon after forest expansion began and have now lost savanna‐typical species. Furthermore, the patterns of termite community composition in fire suppressed savannas support a hypothesis of rapid change driven by fire frequency where either fire suppression or infrequent burning over 23 years has meant savannas have become ecologically much more forest‐like.

Molecular epidemiological study of adenovirus infecting western lowland gorillas and humans in and around Moukalaba-Doudou National Park (Gabon) - Chimène Nze Nkogue; Masayuki Horie; Shiho Fujita; Michiko Ogino; Yuki Kobayashi; Keijiro Mizukami; Tatsunori Masatani; Sayeh Ezzikouri; Aya Matsuu; Tetsuya Mizutani; Makoto Ozawa; Osamu Yamato; et al. (Virus Genes, 2016)

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Biodiversity and conservation genetics research in Central Africa: new approaches and avenues for international collaboration - Nicola M. Anthony; Patrick Mickala; Katharine A. Abernethy; Christiane Atteke; Pulchérie Bissiengou; Michael W. Bruford; Francisco Dallmeier; Thibaud Decaëns; Akaibe Dudu; Adam Freedman; Mary Katherine Gonder; Olivier Hardy; et al. (Conservation Genetics Resources, 2012)

Late-Holocene equatorial environments inferred from deposition processes, carbon isotopes of organic matter, and pollen in three shallow lakes of Gabon, west-central Africa - Pierre Giresse; Makaya Mvoubou; Jean Maley; Alfred Ngomanda (Journal of Paleolimnology, 2009)